2020
DOI: 10.1016/j.ejrad.2020.109309
|View full text |Cite
|
Sign up to set email alerts
|

Combined texture analysis and machine learning in suspicious calcifications detected by mammography: Potential to avoid unnecessary stereotactical biopsies

Abstract: To investigate whether combined texture analysis and machine learning can distinguish malignant from benign suspicious mammographic calcifications, to find an exploratory rule-out criterion to potentially avoid unnecessary benign biopsies. Methods: Magnification views of 235 patients which underwent vacuum-assisted biopsy of suspicious calcifications (BI-RADS 4) during a two-year period were retrospectively analyzed using the texture analysis tool MaZda (Version 4.6). Microcalcifications were manually segmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
0
16
0
4
Order By: Relevance
“…This pretest probability could be determined by malignancy rates associated with BI-RADS features as suggested by the literature [3] which have also been combined into multivariable risk scores [37]. Recently, also machine-learning methods have been employed for risk stratification of breast calcifications [38]. The lack of validation studies and the encouraging results reported here suggest a prospective trial on the clinical use of using breast MRI as an additional test in mammographic BI-RADS 4 microcalcifications to avoid unnecessary biopsies.…”
Section: Discussionmentioning
confidence: 98%
“…This pretest probability could be determined by malignancy rates associated with BI-RADS features as suggested by the literature [3] which have also been combined into multivariable risk scores [37]. Recently, also machine-learning methods have been employed for risk stratification of breast calcifications [38]. The lack of validation studies and the encouraging results reported here suggest a prospective trial on the clinical use of using breast MRI as an additional test in mammographic BI-RADS 4 microcalcifications to avoid unnecessary biopsies.…”
Section: Discussionmentioning
confidence: 98%
“…2 Application of radiomics and AI to improve the diagnostic accuracy of breast imaging. Stelzer et al examined the radiomic signatures of microcalcifications in 235 patients [69]. All findings were assessed as suspicious in conventional visual analysis (BI-RADS IV) and therefore bioptically confirmed.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Therefore, radiomic signatures may be considered accurate, workflow-friendly, and cost effective which is why they provide value to patient care (modified and reprinted with permission [69]). [69]. Alle Befunde wurden in der konventionellen visuellen Analyse (BI-RADS IV) als verdächtig bewertet und daher bioptisch bestätigt.…”
Section: Artificial Intelligenceunclassified
See 1 more Smart Citation
“…For years, numerous studies have been devoted to the early diagnosis of melanoma using various computational methods. Machine Learning techniques as part of Computer-Aided Diagnosis have been applied successfully for the detection of polyps in colonoscopy [ 9 , 10 ], calcifications in mammography [ 11 ], chest imaging [ 12 ], automated solutions for melanoma diagnosis using dermoscopic images [ 13 , 14 , 15 ] and non-invasive methods of recognition of the finger skin [ 16 ]. In another approach, the features extracted from the pixels of a lesion were handled by a Stack-Based Auto-Encoder, and various classification methods like Principal Component Analysis, Recurrent Neural Networks and a Softmax Linear Classifier were utilized for automatic diagnosis of pigmented skin lesions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%